LEKSIKON BUDAYA DALAM SENI TARI TRADISIONAL MELAYU SAMBAS : KAJIAN ETNOLINGUISTIK - Aprialzen, Zanika; Syahrani, Agus; Muzammil, Ahmad Rabi’ul (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
This study aims to inventory and describe in the form of lingual units,lexical meaning and cultural meaning based on the cultural lexicon inthe Sambas Malay traditional dance. The method used in this researchis a descriptive method in the form of qualitative research, and uses anethnolinguistic approach. The data sources in this study were culturaldance activists such as teachers (coaches) and musicians, the data in thisstudy was the traditional Malay Sambas dance. Data collectiontechniques are interview, note, record and documentation. Thetechnique of testing the validity of the data is the persistence ofobservation and triangulation. This research produces 275 lexicon in thetraditional Malay dance Sambas with details of 153 words in the formof monomorphemic and polymorphemic, and 122 phrases. Themeanings found in this study are 275 lexical meanings and 113 culturalmeanings and their components of meaning